2015
DOI: 10.1177/1545968315604396
|View full text |Cite
|
Sign up to set email alerts
|

Variable Intensive Early Walking Poststroke (VIEWS)

Abstract: The present study examined the efficacy of high-intensity, variable stepping training on walking and nonwalking outcomes in individuals 1 to 6 months poststroke as compared with conventional interventions. Methods Individuals with unilateral stroke (mean duration = 101 days) were randomized to receive ≤40, 1-hour experimental or control training sessions over 10 weeks. Experimental interventions consisted only of stepping practice at high cardiovascular intensity (70%-80% heart rate reserve) in variable contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 38 publications
5
107
2
Order By: Relevance
“…For stepping activity, smaller differences between training groups could be due to increased loads or resistance applied to the trunk or limbs to increase HRs. For stepping intensity, however, peak HRs were separated by ~10% predicted HR (70 vs 60% during high- vs low-intensity LT), whereas previous studies manipulating LT intensity in patients post-stroke revealed greater HR differences (18 %HR differences) 35 . The relatively smaller difference was highlighted by blunted HR responses in selected participants regardless of training intensity, and by others with greater HRs than the targeted low-intensity range.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…For stepping activity, smaller differences between training groups could be due to increased loads or resistance applied to the trunk or limbs to increase HRs. For stepping intensity, however, peak HRs were separated by ~10% predicted HR (70 vs 60% during high- vs low-intensity LT), whereas previous studies manipulating LT intensity in patients post-stroke revealed greater HR differences (18 %HR differences) 35 . The relatively smaller difference was highlighted by blunted HR responses in selected participants regardless of training intensity, and by others with greater HRs than the targeted low-intensity range.…”
Section: Discussioncontrasting
confidence: 60%
“…The primary measure of intensity was training HRs, which was monitored continuously using pulse-oximetry, and correlates well with oxygen consumption in intact and impaired individuals. With determination of maximum age-predicted HR (208-(0.7*age), the goal of high-intensity LT was to maintain HRs within 70–85% of predicted maximum HR (HRmax) 35,36 while low-intensity training targeted 50–65% HRmax; these HR ranges approximate those observed during conventional physical therapy 35,42 . If targeted HR zones could not be achieved during training, the Rating of Perceived Exertion (RPE) scale 43,44 was also utilized as a secondary measure of intensity, with targeted ratings of 15–17 (“hard” to “very hard”) for the high–intensity LT protocol and 11–13 (below “somewhat hard”) for low-intensity LT protocol 17,26,35 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study does not demonstrate a therapeutic effect, several benefits can be derived from such an immediate and substantial increase in poststroke walking performance. For example, an immediate improvement in walking capacity may increase the opportunity for walking practice of higher intensity and variability-key ingredients for effective neurorehabilitation (70,81,82). Improved walking capacity may improve self-efficacy and reduce barriers to community engagement (8,51,83).…”
Section: Discussionmentioning
confidence: 99%
“…For example, aerobic capacity effect sizes in previous studies (AEX group change minus control group change) have ranged from −1.5 13 to +6.3 14 mL/kg/min, walking speed effect sizes have ranged from −0.09 15 to +0.25 16 m/s and walking endurance (6-minute walk test) effect sizes have ranged from −25 17 to +89 16 m. An understanding of the factors affecting these between study differences could help inform AEX prescription and prioritize future studies.…”
Section: Main Manuscriptmentioning
confidence: 99%